Mátraaljai őstermelők által használt közvetlen értékesítési csatornák vizsgálata - Janurik, János; Koncz, Gábor (Studia Mundi – Economica, 2015)
The target of our research is to examine the supply channels of products produced and processed locally in the area at the bottom of the Mátra Hills. How results typical nationwide are also typical for this area which type of direct sales is mostly used here. In former studies market mainly traditional market is prior. The second most widespread way of sales is selling from the house or selling on-farm. For farms of producers selling this way is typical to produce several fruits and vegetables are small plant forms and that they do not employ outside workers.